Serous Retinal Detachment in Pre-Eclampsia: A Systematic Review of Case Report - Haikal Hamas Putra Iqra; Meilisva Audila Anggraini; David Giffard Kawi Junior; Marie Yuni Andari; Ario Danianto (Fakultas Kedokteran Universitas Brawijaya, 2023)
Serous Retinal Detachment is one of the preeclampsia complications which may be identified during the third trimester of pregnancy or postpartum period that may be related to pregnancy condition. We review case reports related to serous retinal detachment in preeclamptic patients from online databases such as MEDLINE/Pubmed and Science Direct from 2011 to 2021 in accordance with PRISMA guidelines. Authors independently screened abstracts of articles retrieved articles that were considered potentially relevant, and extracted the articles obtained. From 17 articles, serous retinal detachment is higher in severe preeclampsia and HELLP syndrome (88%). Most patients were indicated to do caesarean section (71%) as their mode of delivery due to managing severe preeclampsia. Although most patients (94%) reported retinal detachment involving the macular area, complete resolution was observed in all the patients (94%). Early detection of serous retinal detachment may increase awareness of early detection of severe preeclampsia and HELLP syndrome.